Surgical observation on the study of anatomy in medical students: A systematic review. - Garrido Candia, Verónica Alejandra; Sáez Terrazas, María José; Salinas Leiva, Catalina Alejandra; Rojas Pino, Marcos (Spanish Journal of Medical Education, 2022)
As a result of globalization and the global health context due to the Covid-19 pandemic, the study of anatomy in medical students has had to reinvent itself by incorporating new techniques to enhance learning, among which the observation of surgical videos stands out. The objective of this review is to determine whether remote observation of surgeries has a positive impact on anatomy learning in medical students. Methods: A systematic review of the existing literature in the WOS and SCOPUS databases was carried out using the PRISMA protocol. Studies published in English and Spanish were considered. Three authors reviewed the full texts and selected data related to the visualization of surgical videos and their impact on anatomy learning. Subsequently, the information obtained was synthesized and reviewed according to the PRISMA protocol. Results: Four studies met the inclusion criteria. In all the selected studies, the students' perception of this new methodology was evaluated, to which they stated that it was useful and a positive experience. Two of the studies carried out an objective evaluation of the knowledge acquired and in both there were better results in the group that applied this methodology. In addition, all the studies recommended using video viewing in a complementary way to the methodologies used today. Conclusions: Remote observation of surgeries could have a positive impact on the training of future physicians. It is necessary to continue investigating the possible effects of this new methodology in order to determine whether its implementation is effective, since the literature on this subject is limited.